2018
DOI: 10.1177/0004867418785036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of psychotic experiences in a nationally representative sample of Australian adolescents

Abstract: Hallucinatory and delusional experiences are common in Australian adolescents. Hallucinatory experiences, rather than delusional experiences, may be more clinically relevant in this demographic. When psychotic experiences are endorsed by adolescents, further assessment is indicated so as to ascertain more detail on the phenomenology of the experiences to better understand their clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Melancholic features are extremely rare and invite a search for an organic cause such as prolactinoma. Hallucinations may be reported but are often a marker of traumatic experiences rather than psychosis (Hielscher et al, 2018; Nam et al, 2016). Finally, death by suicide is very uncommon in prepubertal children, but many depressed children harbour suicidal thoughts.…”
Section: Classificationmentioning
confidence: 99%
“…Melancholic features are extremely rare and invite a search for an organic cause such as prolactinoma. Hallucinations may be reported but are often a marker of traumatic experiences rather than psychosis (Hielscher et al, 2018; Nam et al, 2016). Finally, death by suicide is very uncommon in prepubertal children, but many depressed children harbour suicidal thoughts.…”
Section: Classificationmentioning
confidence: 99%
“…More importantly, studies have suggested that the psychotic pathway commences with what is referred to as psychotic-like experiences (PLEs) [ 13 ]. PLEs are subclinical symptoms of psychosis that do not meet the threshold for clinical diagnosis as psychotic illness [ 13 , 14 ]. PLEs are very common in the general population, appearing first in adolescence and sometimes in childhood [ 15 ] and can be categorized as positive (e.g., perceptual abnormalities, delusional thoughts) or negative (e.g., social withdrawal, avolition) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Often referred to as psychotic-like experiences, hallucinations and delusions that occur in the absence of a psychotic disorder are not uncommon in the general population (Van Os et al 2009, Kelleher et al 2012a. Although many individuals who experience hallucinations or delusions do so in the absence of any mental disorder (Peters et al 2016), higher rates of both concurrent and later mental disorder have been found in young people who report these phenomena (Kelleher et al 2012b, DeVylder et al 2014, Kelleher et al 2015, Waters et al 2017, Healy et al 2018b, Hielscher et al 2018, Carey et al 2020. For this reason, young people with a history of hallucinations and delusions represent a unique and important group for ongoing research into the relationship between these phenomena and psychopathology.…”
Section: Introductionmentioning
confidence: 99%